Evaluation of the Vocational Education Orientation Programme (VEOP) at a University in South Africa - Jacobs, Lynette; De Wet, Corene (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
To address the training needs of Further Education and Training college (FETC) lecturers, and in the absence of a full professional education qualification, several higher education institutions, FETCs, and other bodies in South Africa formed an alliance to develop a short programme towards a possible future full qualification. In 2010 a Vocational Education Orientation Programme (VEOP) was piloted. In line with the responsibility for quality assurance, and the need to inform further developments in the training of FETC lecturers, the aim of this research was to evaluate the VEOP presented by the University of the Free State (UFS). To reach the stated aim, a two phase evaluative study was undertaken (1) to assess the individual modules, and (2) to holistically investigate the quality of the programme. Two questionnaires were used to gather data. The first set of data was collected at the completion of each of the six modules. For the second phase of the study, 48 lecturer-students were randomly selected more than a year after completion of the VEOP. The study identified a number of strengths and weaknesses of the VEOP. The results emphasise the need to carefully select tutors and train them to have an understanding of the FETC milieu, rethink the methodology employed in the education training of FETC lecturers, and redesign the modules’ contents to better reflect the FETC sector. The need to enhance student support and improve administration is also highlighted by the study. The results of the study may inform the development of a full qualification for FETC lecturers.